LEECH: A 100 Night Exoplanet Imaging Survey at the LBT. Issue Volume 8:Issue S299(2013) (6th January 2014) - Skemer, Andrew; Apai, Daniel; Bailey, Vanessa; Biller, Beth; Bonnefoy, Mickael; Brandner, Wolfgang; Buenzli, Esther; Close, Laird; Crepp, Justin; Defrere, Denis; Desidera, Silvano; Eisner, Josh; et al.
Abstract: In February 2013, the LEECH (LBTI Exozodi Exoplanet Common Hunt) survey began its 100-night campaign from the Large Binocular Telescope atop Mount Graham in Arizona. LEECH neatly complements other high-contrast planet imaging efforts by observing stars in L' band (3.8 microns) as opposed to the shorter wavelength near-infrared bands (1–2.3 microns). This part of the spectrum offers deeper mass sensitivity for intermediate age (several hundred Myr-old) systems, since their Jovian-mass planets radiate predominantly in the mid-infrared. In this proceedings, we present the science goals for LEECH and a preliminary contrast curve from some early data.